Trace Metal Imaging of Sulfate-Reducing Bacteria and Methanogenic Archaea at Single-Cell Resolution by Synchrotron X-Ray Fluorescence Imaging. Issue 1 (2nd January 2018) - Glass, Jennifer B.; Chen, Si; Dawson, Katherine S.; Horton, Damian R.; Vogt, Stefan; Ingall, Ellery D.; Twining, Benjamin S.; Orphan, Victoria J.
ABSTRACT: Metal cofactors are required for many enzymes in anaerobic microbial respiration. This study examined iron, cobalt, nickel, copper, and zinc in cellular and abiotic phases at the single-cell scale for a sulfate-reducing bacterium ( Desulfococcus multivorans ) and a methanogenic archaeon ( Methanosarcina acetivorans ) using synchrotron X-ray fluorescence microscopy. Relative abundances of cellular metals were also measured by inductively coupled plasma mass spectrometry. For both species, zinc and iron were consistently the most abundant cellular metals. M. acetivorans contained higher nickel and cobalt content than D. multivorans, likely due to elevated metal requirements for methylotrophic methanogenesis. Cocultures contained spheroid zinc sulfides and cobalt/copper sulfides.